Bilateral fibrosarcoma of the epididymis. Issue 7 (July 1975) - McCormack, M
Abstract : The tenth case of primary fibrosarcoma of the epididymis is reported. Contrary to most previous cases, excision biopsy was followed by a lengthy tumour-free period, and a unique feature was bilateral epididymal recurrence.